PEMANFAATAN TEKNOLOGI INFORMASI UNTUK PENGEMBANGAN USAHA INDUSTRI KECIL MENENGAH (STUDI KASUS PADA IKM DEWI RATIH) - Suryadi - Poerbo (Politeknik Negeri Semarang, 2014)
Batik small business at Sragen is one of special business which has high value added in the industries. On other side, the owner of batik small business do not ready to entry to the international market. They have any barrier to develop that business.IKM Batik Dewi Ratih is one of small business at Batik Village Tourism, Sragen. It has very little bit skill in computer literacy. The business is running by conventional or traditional management, especially by family management style. The owner of IKM does not have educational background in global market, so just think regional market. Team from Polines develop business IKM to entry to the international market, on three stream of management area, ie. inventory, sales administration, and marketing.IKM needs any devices to increase its performance, ready to entry to the global market, for example: computer, cd-rewriter, business software applications, digital catalogue.